THE USE OF LEXICAL COLLOCATIONS IN SOME ARTICLES OF SEVENTEEN.COM WEBSITE - Marsya Aprila Tayibnapis; Lina Meilinda; Yessy Purnamasari (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2021)
Collocations are one of the problems faced by EFL (English as a Foreign Language) learners when learning English language. This study is intended to help the EFL Learners and non-native English speakers to add knowledge about collocations. Therefore, this study is aimed to find the use of lexical collocations and their meaning. This study used a descriptive qualitative research technique. The source of the data is eleven articles from eight sections in seventeen.com. om the research, there were 79 lexical collocations and they were classified as six out of seven types that Benson et al. (2010) proposed. The data showed that the most used type is L3 (adjective + noun) and the least used is L4 (noun + verb). The meaning of the lexical collocations was defined from the contexts.